Desain Kebijakan Sistem Informasi dan Teknologi Informasi Dengan Framework Zachman Pada Perguruan Tinggi Negeri Baru di Jakarta - Indra Permana Solihin; M. Bayu Wibisono (Ikatan Ahli Informatika Indonesia (IAII), 2017)
Design policy at UPN Veteran Jakarta, which can enhance the competitiveness, effectiveness and efficiency, to reach UPN Veteran Jakarta vision, mission and objectives. The methodology used Enterprise Architecture Planning (EAP) with approximate Zachman Framework. Consequences that were achieved from the research were to make a framework of the integrated strategic IS and IT planning to facilitate the information management needed. The conclusion of this research is the proposed IS/IT strategic planning framework which could be implemented and used in the UPN Veteran Jakarta in the future.